System dynamics modeling in designing breeding schemes: The case of Menz sheep in Ethiopian highlands - Gebre, K.T.; Wurzinger, Maria; Gizaw, Solomon; Haile, Aynalem; Rischkowsky, Barbara A.; Getachew, T.; Sölkner, Johann (Oxford University Press, 2017)
A comprehensive dynamic simulation model was developed to describe a community-based breeding program for the Menz sheep population of Ethiopia. Selection of male and female animals based on their own and maternal performance was simulated. The breeding goal traits were 6-mo weight, preweaning survival, and fertility rate. The model input data were obtained from the flock book, questionnaires, and references. The simulation model used a mix of deterministic and stochastic procedures to model the complex system. In the baseline scenario, the proportion of selected male and female animals varied between 20 and 30% and between 70 and 80%, respectively. A reasonable annual genetic gain was predicted for the breeding goal traits at the village level. For 6-mo weight and preweaning survival rate, the annual genetic gain varied from 0.213 to 0.214 kg and 0.255 to 0.256%, respectively. For fertility rate, an annual genetic gain of 0.063% was obtained. The predicted rate of inbreeding per year was between 0.094 and 0.116%. Furthermore, a scenario analysis was conducted by varying the proportions of selected animals. Annual genetic gains of 0.230 kg, 0.277%, and 0.069% were obtained for 6-mo weight, preweaning survival rate, and fertility rate, respectively, when the proportion of selected male and female animals decreased by 10%. The annual genetic gains decreased to 0.198 kg, 0.236%, and 0.059%, respectively, when the selection proportion of male and female animals increased by 10%. The lowest rate of inbreeding per year, ranging from 0.065 to 0.079%, was achieved when the selection proportion of selected male and female animals increased. The model is relevant for the step-by-step evaluation of more than one round of selection. It is flexible and usage driven. The model is a valuable tool to design different population structures and can be easily expanded to adopt different breeding strategies. Hence, the system dynamics modeling approach is a potential tool to describe complex breeding programs.